FinGo flashcard: teaching society to use e-wallet / Muhammad Amir Amran ... [et al.] - Amran, Muhammad Amir; Md Hartika, Muhammad Hasif; Rosle, Muhammad Suhaimi; Abdul Rahman, Abdul Azim; Koe, Wei Loon (Universiti Teknologi MARA, Kedah, 2023)
FinGo Flashcards is a flashcard quiz related to financial planning. There are many people spending their expenses without doing any record, especially when they use cash. Besides using cash, people nowadays has started to use e-wallet because on e-wallet also allow them to do investment and insurance. A survey on e-wallet usage by Oppotus showed a decrease in use of e-wallet. There are still many people do not know how to use e-wallet. There are various limitations in e-wallet, such as lack of instruction, too many features, and a bit of complexity, which causes people such as millennials and boomers to be unfamiliar with ewallets. Therefore, the objectives of FinGo Flashcard is to educate individuals to use e-wallet, specifically Touch and Go (TNG) e-wallet it is also aimed to improve financial literacy among society, help individuals reach their financial goals, make strategies that keep them accountable to their finances and know how to budget and save their money. FinGo Flashcards has various uniqueness such as being easy to understand and suitable for the use of the old generation, colourful in design, full of information specially focusing on TNG e-wallet and it is specially made for hand carry so that it can be used anywhere you go. The benefits of FinGo Flashcard are such as people understand the function of using TNG e-wallets and make investments and buy insurance using TNG e-wallet. The target market is the old generation and fresh graduates that are still using cash as the main tools for making payments by using TNG e-wallet.